Dari Pendapingan Menuju Kemandirian: Pemberdayaan Komunitas dalam Program Senam Sehat Bersama - Eli Retnowati; Ernawati Ernawati; Achmad Hayden Syafaat Putra; Achmad Ghoni Ken Diyu; Muhammad Syairul Fitra (Komunitas Manajemen Kompetitif, 2026)
This community service program is motivated by the importance of sustaining community-based physical activity to improve public health, particularly after the mentoring phase ends. In the initial stage, a healthy exercise program conducted in Pagesangan Village, Surabaya, successfully increased community participation and awareness of the importance of physical fitness. However, the main challenge lies in the community’s ability to maintain the program independently. Therefore, this second-stage program aims to analyze and strengthen community independence through a community empowerment approach. The method used is a participatory approach involving post-assistance evaluation, strengthening local leadership, and facilitating independent program management. The results show that the community has successfully established a self-managed group called “Senam Sehat Bersama,” equipped with an organizational structure, local instructors, regular exercise schedules, and a self-sustaining funding system through member contributions. These findings indicate that continuous mentoring effectively fosters community independence. Thus, this program provides significant implications as a sustainable community-based health empowerment model that can be replicated in other regions.